Miniaturizing optical coherence tomography. Issue 1 (8th January 2022) - Rank, Elisabet A.; Agneter, Anja; Schmoll, Tilman; Leitgeb, Rainer A.; Drexler, Wolfgang
Abstract: Optical coherence tomography (OCT) has revolutionized ophthalmic diagnosis as a non‐invasive, cross‐sectional imaging technique in the last 30 years and hence is one of the fastest adopted advanced imaging technologies in the history of medicine. A miniaturization of OCT devices would not only reduce size but ideally also reduce costs and therefore create potential new markets. OCT systems based on photonic integrated circuits (PIC) could enable a significant miniaturization of complex systems with high degree of integration as well as low costs of goods. These therefore have a potential to enable portable, cost‐effective, high performing, real handheld OCT devices. This review identifies three main categories towards miniaturized OCT devices: Handheld imaging probes interfaced to a (mobile) base station, compact home/self‐ OCT and PIC‐based OCT. Imaging performance parameters and technical readiness levels of the identified miniaturized OCT systems for (non‐) ophthalmic applications are presented. Special attention is paid to PIC‐based OCT applications and their progress. Picture : First in vivo human retinal tomogram using a PIC‐based subcomponent (arrayed waveguide grating, AWG) of a spectral domain OCT system. Adapted with permission from E. A. Rank et al., Light Sci Appl . 2021, 10, 1, CC By 4.0. Copyright © 2021, The Author(s). Abstract : The miniaturization of optical coherence tomography (OCT) is gaining increasing scientific as well as commercial attention. A literature search reveals 70+ articles reporting on systems towards handheld, more compact and more cost‐effective ways to build OCT devices, potentially enabling new markets. Technical readiness levels and reported imaging performance are used to discuss achievements in OCT using handheld‐probes, compact home‐/self‐OCT and photonic integrated circuits‐ based OCT. (Figure adapted with permission from E. A. Rank, R. Sentosa, D. J. Harper, et al., Light Sci Appl . 2021, 10, 1. CC By 4.0. Copyright © 2021, The Author(s))